Bullying and cyberbullying between theoretical foundations and empirical evidence. The results of a knowledge survey on preadolescents. - Zbigniew Szczepan Formella; Letizia Cavalli (Seminare, 2022)
The paper presents a cognitive investigation in which were involved 501 preadolescents in the town of Frosinone. In the complex issue of bullying and cyberbullying, we want emphasise the primacy of the experienced virtual prevarications through the traditional modes, often in continuity with the electronic form. The survey shows that twelve-year old youngsters were more involved in episodes of bullying. Compared to the asymmetric relationships, the results highlight the centrality of the significant adults, such as teachers and parents, as principal interlocutors on the phenomenon of prevarication, both traditional and virtual. Through the survey, we were able to trace the educational needs and to propose the resources for the preadolescents in order to plan some specific preventive interventions, specifically contrasting therefore more effective.